Synthesis and characterization of local biomass supported magnetic catalyst for esterification reaction - Krishnan S.G.; Pua F.-L.; Jaafar S.N.S. (Elsevier Ltd, 2023)
Biomass; Catalysis; Catalyst supports; Esterification; Esters; Fourier transform infrared spectroscopy; Fruits; Hematite; Magnetism; Palm oil; Scanning electron microscopy; X ray diffraction; Empty fruit bunches; Esterification reactions; Magnetic; Oil palm; Oil palm empty fruit bunch; Solid catalysts; Support materials; Synthesis and characterizations; X- ray diffractions; ]+ catalyst; Oleic acid